Correlation between Learning Interest with Student's Learning Achievement in Islamic Religion (Case Study of MTs.S Teupah Barat) - Afriani S; Ayel Sarwono Lahra; Trisosiana Lefia; Siti Lesnita (Budapest International Research and Critics University, 2022)
Interest is a tendency to pay attention continuously, which serves as a force that will encourage someone to learn. Students who are interested in the lesson will be seen students to be diligent in learning. The role of interest is to improve student learning achievement. If students have a high interest, their level of learning achievement will produce high scores. Learning achievement is evidence of the efforts that have been made in teaching and learning activities and is the value obtained by students from the learning process that has been taken. The formulation of the problem in this study is